Peranan Orang Tua Dalam Pembinaan Pendidikan Karakter Anak Di Nagari Tigo Jangko Kecamatan Lintau Buo - Silvia Anggreni (IJOCE: Indonesia Journal of Civic Education, 2020)
This study aims to determine the role of parents in fostering children's character education in Nagari Tigo Jangko, Lintau Buo District. This type of research is qualitative research with parents who have children aged 7-16 years and children aged 7-16 years taken by purposive sampling. The type of research data is primary data and secondary data. Data collection techniques used were interviews and documentation. The data analysis technique used is data collection, data reduction and drawing conclusions. The technique of testing the validity of the data is done through triangulation. The results showed that the role of parents in fostering children's character education in Nagari Tigo Jangko, Lintau Buo Subdistrict was (a) Instilling discipline in children since childhood (since their children entered elementary / elementary school), (b) Providing direction in religious education such as praying and assessing, (c) Guiding and directing children to carry out their responsibilities in completing homework (PR). Conclusions that parents have instilled character education in children such as discipline since childhood, learning to recite, and guide to be responsible. Keywords: Parents, Character Education.